Effect of biofilm coatings at metal-oxide/water interfaces I: Pb(II) and Zn(II) partitioning and speciation at Shewanella oneidensis/metal-oxide/water interfaces. (1st September 2016) - Wang, Yingge; Gélabert, Alexandre; Michel, F. Marc; Choi, Yongseong; Gescher, Johannes; Ona-Nguema, Georges; Eng, Peter J.; Bargar, John R.; Farges, Francois; Spormann, Alfred M.; Brown, Gordon E.
Abstract: Microbial biofilms are often present as coatings on metal-oxide surfaces in natural and industrial environments and may induce significant changes in the partitioning behavior and speciation of aqueous metal ions, which in turn can impact their transport and fate. In this study, long-period X-ray standing wave-fluorescence yield (LP-XSW-FY) spectroscopy was used to measure under in situ conditions the partitioning of aqueous Pb(II) and Zn(II) between multilayer Shewanella oneidensis MR-1 biofilms and highly polished, oriented single-crystal surfaces of α-Al2 O3 and α-Fe2 O3 as a function of metal-ion concentration and time at pH 6.0. We show that after 3-h exposure time, Pb(II) binds preferentially to the α-Al2 O3 (1–102) and α-Fe2 O3 (0 0 0 1) surfaces at low Pb concentration ([Pb] = 10 −7 M) and then increasingly partitions into the biofilm coatings at higher concentrations (10 −6 to 10 −4 M). In contrast, Zn(II) partitions preferentially into the biofilm coating for both surfaces at all Zn concentrations studied (10 −7 to 10 −4 M). In comparison, the α-Al2 O3 (0 0 0 1) surface has a low affinity for both Pb(II) and Zn(II), and the biofilm coatings are the dominant sink for both ions. These findings suggest that in the presence of S. oneidensis biofilm coatings, α-Al2 O3 (0 0 0 1) is the least reactive surface for Pb(II) and Zn(II) compared to α-Al2 O3 (1–102) and α-Fe2 O3 (0 0 0 1). They also show that Zn(II) has a lower affinity than Pb(II) for reactive sites on α-Al2 O3 (1–102) and α-Fe2 O3 (0 0 0 1) at [Me(II)] of 10 −7 M; at 10 −5 M, the bulk of the metal ions partition into the biofilm coatings. At longer exposure times (20–24 h), both Pb(II) and Zn(II) increasingly partition to the metal-oxide surfaces at [Me(II)] = 10 −5 M and pH 6.0, indicating possible reaction/diffusion-controlled sorption processes. Pb LIII -edge and Zn K-edge grazing-incidence extended X-ray absorption fine structure (GI-EXAFS) measurements suggest that both Pb(II) and Zn(II) ions may be complexed by carboxyl groups in S. oneidensis biofilms after 3-h exposure at pH 6.0 and [Me(II)] = 10 −5 M. In contrast with Burkholderia cepacia, which was used in our previous studies of monolayer biofilm-coated metal-oxide surfaces (Templeton et al., 2001), S. oneidensis MR-1 forms relatively thick biofilm coatings (6–20 μm) that are rich in reactive functional groups and are expected to dominate metal-ion adsorption. Our results show that even thick and highly reactive biofilms like S. oneidensis do not cause much change in the intrinsic chemical reactivities of the underlying metal-oxide surfaces with respect to aqueous Pb(II) and Zn(II) and don't block reactive sites on the metal-oxide surfaces; instead they reduce the rate of Pb(II) and Zn(II) sorption onto these surfaces.